2021
DOI: 10.3390/w13070969
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Remediation of Desalination Plant Outfall Brine Discharge from Heavy Metals and Salinity Using Halloysite Nanoclay

Abstract: Halloysite (HS) nanoclay was used for the environmental treatment of desalination brine water discharge via the adsorptive removal of selected heavy metals ions; zinc, iron, nickel, and copper, as well as salinity. Different techniques were used for the characterization of the HS nanoclay and it was found that HS nanoclay exists as transparent hollow nanotubes with high surface area. The study showed that most of the heavy metal ions could be removed successfully using the HS nanoclay in a few minutes, at norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Table 2 shows the main composition of physicochemical parameters present in ROC from desalination plants (seawater or brackish). Some authors have shown the structural characteristics of brine components using FTIR, SEM, and TEM [42][43][44]. Furthermore, Sanmartino et al [45] identified the phases present in the used RO brine by semi-quantitative analysis of the characteristic peaks obtained for X-ray diffraction, such as NaCl (67%), MgCl 2 •6H 2 O (15%), CaSO 4 (10%), Mg 3 (SO 4 ) 2 (OH) 2 (3%), Na 2 SO 4 (3%), and CaMg(CO 3 ) 2 (2%).…”
Section: Physicochemical Characteristics Of the Rocmentioning
confidence: 99%
“…Table 2 shows the main composition of physicochemical parameters present in ROC from desalination plants (seawater or brackish). Some authors have shown the structural characteristics of brine components using FTIR, SEM, and TEM [42][43][44]. Furthermore, Sanmartino et al [45] identified the phases present in the used RO brine by semi-quantitative analysis of the characteristic peaks obtained for X-ray diffraction, such as NaCl (67%), MgCl 2 •6H 2 O (15%), CaSO 4 (10%), Mg 3 (SO 4 ) 2 (OH) 2 (3%), Na 2 SO 4 (3%), and CaMg(CO 3 ) 2 (2%).…”
Section: Physicochemical Characteristics Of the Rocmentioning
confidence: 99%